PADDY RESIDUE AS FEEDSTOCK IN ELECTRICITY GENERATION: REDEMPTION OF LIFE CYCLE EMISSIONS AND COST ANALYSIS (Journal of Technology and Operations Management, 2018)
Malaysia has an abundance of biomass resources that can be utilised for power generation. One of them is paddy residue. Paddy residue creates a huge potential in the power generation sector. The consumption of paddy residue can help Malaysia become less dependent on conventional sources of energy, mitigate greenhouse gas (GHG) emission, offer positive feedback in the economic sector, and at the same time, provide the best solution for waste management activities. The forecast data for 20 years on electricity generation was used to calculate the GHG emission and its saving when paddy residue is used for electricity generation. The government’s cost saving was also identified when paddy residue substituted coal fuel in electricity generation. This paper can provide forecast information so that Malaysia is able to move forward to apply paddy residue as feedstock in energy supply. Hopefully, the data achieved can encourage stakeholder bodies in the implementation of paddy residue in electricity generation since there is a positive impact towards cost and emission saving.